Transforming Clinical Practice Initiative Boosted Participation in Medicare Alternative Payment Models. Issue 3 (July 2022) - Zurovac, Jelena; Barna, Michael; Merrill, Angela; Zickafoose, Joseph S.; Felt-Lisk, Sue; Vollmer Forrow, Lauren; Gallegos, Karen Frederick; Everhart, Damian; Flemming, Robert
Abstract : The Centers for Medicare & Medicaid Services' (CMS's) Transforming Clinical Practice Initiative (TCPi) was the largest national-scale practice transformation model. We analyzed the effect of TCPi on new enrollment into Medicare Alternative Payment Models (APMs) through January 2020 (3 months after program end), using 6958 physician practices enrolled in TCPi and a closely matched comparison group of 6958 practices. More TCPi practices enrolled in Medicare APMs and Medicare Advanced APMs relative to comparison practices overall and in subgroups, including rural, small, and specialty practices. Results suggest that large-scale technical assistance can boost participation in Medicare APMs for a diverse set of practices.